2017
DOI: 10.1055/s-0037-1601397
|View full text |Cite
|
Sign up to set email alerts
|

Digital Myopericytoma: A Case Report and Systematic Literature Review

Abstract: A myopericytoma (MP) is an exceedingly rare perivascular tumor of unknown etiology. Given their potential for mimicry and malignancy, MP tumors pose a unique challenge for surgeons and may be overlooked on differential diagnosis. We present a case report of an otherwise healthy 33-year-old right-hand dominant male who presented to our outpatient clinic with a 2-month history of painless swelling and erythema of the pulp of his left index finger. Subsequent plain film X-ray showed near-complete bony destruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Incisional biopsy was done, and it revealed cellular characteristics of MCP. The patient was treated with left index finger tumor resection with local advancement flap closure [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Incisional biopsy was done, and it revealed cellular characteristics of MCP. The patient was treated with left index finger tumor resection with local advancement flap closure [13] .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of MPCs in the hand is uncommon. In a systematic review and case report by Morzycki et al, only 22 cases of hand and wrist MPCs were reported, with just six previous cases located in the finger [ 5 ]. A more recent review by Lim et al in 2022 described an additional two cases of finger MPCs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%